The recognition and protection of customary law communities in maintaining culture as a tourist attraction in Sembalun village East Lombok - Mahawira, Komang; Muhtasom, Ali; Satiadji, Amirosa Ria; Caraka, Rezzy Eko; Royanow, Achlan Fahlevi (International Journal of Innovative Research and Scientific Studies, 2025)
The rapid growth of tourism and advancements in information technology are influencing the culture of communities in tourist destinations. Sembalun Village, situated on the slopes of Mount Rinjani on Lombok Island, Indonesia, is a suitable example of a community that has successfully preserved its cultural heritage and remains a compelling tourist attraction through generations. Therefore, this study aimed to explore how customary law communities in Sembalun Village are recognized and protected to maintain culture as a tourist attraction in East Lombok, West Nusa Tenggara. By using a descriptive juridical method, the study obtained data through observation, interviews, and documentation. The results showed that the West Nusa Tenggara Provincial Government recognized and protected customary law communities as legal entities. This study further contributed to academic knowledge by enhancing theoretical insights and providing valuable literature for studies on the recognition and protection of customary law communities in the context of cultural preservation as a tourist attraction. Additionally, the practical implications of this study offered guidance for stakeholders, specifically in shaping policies related to the recognition and protection of customary law communities in maintaining cultural heritage for tourism.